Dead men's secrets. M19, Escape and evasion in Europe [videorecording (DVD)] - Martin, Jonathan; May, Aaron (A & E Television Networks : Nugus/Martin Productions : History Channel : Distributed by New Video, 2007)
M19, a little known top secret agency of the Allied war machine and one of World War II's greatest secrets, helped over 7000 British and American prisoners of war escape from Nazi-held territory and POW camps by teaching the soldiers how to withstand interrogation and how to escape and prevent recapture.